Conservation Genomics of a Threatened Rhododendron: Contrasting Patterns of Population Structure Revealed From Neutral and Selected SNPs - Liu, Detuan; Zhang, Lu; Wang, Jihua; Ma, Yongpeng (Frontiers in Genetics, 2020)
Though it is well acknowledged that next generation sequencing (NGS) technologies can provide further insights into plant conservation management than traditional molecular markers, studies employing NGS to address conservation genomics and subsequent conservation strategies for threatened plants are still rare. Rhododendron is the largest genus of woody plants in China, and many species are threatened, however to date there has been no conservation genetic research using NGS in this genus. In the present study, we investigated the conservation genetics of R. cyanocarpum, a threatened species endemic to the Cangshan Mountains in Yunnan, China, using a double digest restriction-site-associated DNA-sequencing (ddRAD-seq) approach. Due to the availability of sufficient SNPs, we were able to distinguish between neutral and putatively selected SNPs and were able to further investigate the genetic diversity, population structure and differentiation in R. cyanocarpum, as well as make an estimation of its demographic history. A total of 6,584 SNPs were obtained, of which 5,729 were neutral (detected using Tajima’s D). In terms of the 5,729 neutral SNPs, R. cyanocarpum had a higher genetic diversity (π = 0.0702±0.0017, He = 0.0675±0.0016) than other plant species assessed using Rad-seq methods, while population differentiation (Fst from 0.0314 to 0.0452) was weak. Interestingly, contrasting patterns of population structure were revealed from all, neutral and selected SNPs, with distinct genetic clusters forming for all SNPs and neutral SNPs, but no distinct subgroups for selected ones. Moreover, we were able to detect changes in effective population size (Ne) of R. cyanocarpum from 150,000 years ago, including a bottleneck event ca. 60,000 years ago, followed by recovery of Ne over a short period, and a subsequent gradual decline in Ne to date. Implications for conserving R. cyanocarpum based on these main results are then discussed.